Immigrants gais au Québec face à l’homophobie : possibilités, contraintes et implications pour leur bien-être - Claudia Fournier; Louise Hamelin Brabant; Sophie Dupéré; Line Chamberland (Genre, Sexualité et Société)
This article aims to describe the opportunities and constraints with which immigrant gay men, aged 20 to 35 years old and living in the Province of Quebec (Canada), face homophobia and heterosexism in post-migratory context. We focus on their experiences related to homophobia and the expression of their sexual orientation, and the implications for their well-being. Results from our qualitative study with 25 participants show that these men consider they have gained new opportunities to express their sexual orientation after migrating to the province of Quebec, but that they are still affected by the more or less insidious effects of homophobia and heterosexism. They use three main strategies to face them: trying to avoid being identified as gay; ensuring they stay in spaces that are free from homophobia; and attempting to be accepted despite heterosexist norms. Implications for their well-being are also discussed.